Pengaruh Penggunaan Media Sosial Tiktok Terhadap Gaya Hidup Berpakaian Remaja Ilkom Untidar - Adelia Regina Damayanti; Linda Anjarsari; Namira Anjani (CV. ITTC INDONESIA, 2022)
The development of the current era, giving influence to all existing fields. One of them is the development of information technology, information technology is also growing rapidly. The rapid development of information technology and the development of the internet has led to the development of social media. In Indonesia, most people use social media for various reasons, one of which is Tiktok. The research method used is quantitative. Data analysis used to test the hypothesis in this study is to use a Simple Linear Regression Test. A simple linear test is used to determine the effect of the independent variables on the dependent variable. Based on the tests that have been carried out, it shows that there is an influence between variable X on variable Y with a significance level of 0.000 <0.05, which means that Tiktok Social Media has an influence on the lifestyle of teenagers dressed in the Science of Communication at Tidar University.